Conceptualization and measurement of physiologic health for adults. Vol. 12, vision impairment - Rubenstein, Randi S.; Lohr, Kathleen N., 1941-; Brook, Robert H. (Robert Henry), 1943-; Goldberg, George A., 1941-; Rand eBooks (Santa Monica, CA : RAND, 1982)
The Health Insurance Study (HIS) will use data on impaired vision to study the relationship of health insurance to health status and quality of medical care. Impaired eyesight was selected as a health indicator because it is highly prevalent, easy to measure, and improvable in most cases. This report establishes criteria for measuring the prevalence and adverse effects of vision impairment and it defines criteria for evaluating medical care; it analyzes the data on prevalence and adverse effects among the HIS population; and it verifies that enrollee assignment to different health insurance plans had been random. A medical screening examination and a medical history questionnaire, both administered at the time of enrollment, provided data for this study. Results from the screening examination retesting for near and far vision confirmed that the HIS testing procedures were reliable.
"July 1982."
Includes bibliographical references (p. 105-109).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Chronic diseases -- United States -- Statistics; Health status indicators -- United States; Health surveys -- United States; Insurance, Health -- United States -- Statistics; Vision disorders -- United States; Chronic Disease -- Adult; Health Surveys -- United States; Insurance, Health -- United States; Vision Disorders -- epidemiology -- United States; Electronic books